Treatment of Pathological Fracture Following Unicameral Bone Cyst in Unusual Location of Proximal Radius: Rare Case Report: Treatment of Unicameral Bone Cyst in Unusual Location of Proximal Radius: Rare Case Report (World Journal of Current Medical and Pharmaceutical Research, 2023)
Unicameral bone cysts (UBCs) are benign bone lesions predominantly affecting children and teenagers. This case report highlights the rare occurrence of a simple bone cyst in the proximal radius in  a 29-year-old woman with a pathological fracture. Although the proximal radius is an uncommon site for UBC occurrence, the surgical approach required special care due to the complex anatomical structures near the fracture site. The surgical management of UBCs  aims to prevent or manage pathological fractures, facilitate cyst healing, prevent recurrence, and reduce the risk of refracture.  Understanding the treatment options and involving patients in the decision-making process are crucial for achieving the best possible results in managing UBCs with pathological fractures. The decision to pursue nonoperative or operative treatment should be made in consultation with healthcare professionals, considering factors such as clinical presentation, radiological features, and symptoms.